Penilaian Efisiensi Saham Syari’ah dengan Pendekatan Shari’a Compliant Asset Pricing Model pada Jakarta Islamic Index - Abdurrohman Abdurrohman; Diharpi Herli Setyowati; Tjetjep Djuwarsa (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The purpose of this study is to analyze the efficiency of Islamic stocks in several companies which are listed on the Jakarta Islamic Index (JII) from January 2014 to November 2018. This study uses the Shari'a Compliant Asset Pricing Model (SCAPM) method modification of the Capital Asset Pricing Model (CAPM) to be appropriate with sharia principles. The variables of this study are Stock Return (Ri), Market Return (Rm), Stock Beta (β), SBIS Yields, Requred Rate of Return (RRR). The sample in this study is determined by using purposive sampling. This research is a type of descriptive quantitative research and data collection technique is from the documentation of secondary quantitative data, then they are all processed by Microsoft Excel. The results of this study, from 12 samples of sharia stocks shows that there are 7 sharia stocks classified as efficient and 5 sharia stocks classified as inefficient.